Pseudomonas Aeruginosa An Armory Within - Sriramulu, Dinesh (IntechOpen, 2019)
Pseudomonas aeruginosa, though unfamiliar as an aggressive invader, has gained importance in the scientific community due to its association with cystic fibrosis (CF) and its ability to construct biofilms resilient to host defense. The chronic nature of CF allows this bacterium to colonize, adapt, and evolve at its own pace, thereby causing further complications in CF patients. With its huge genetic repertoire and plasticity of the genome, P. aeruginosa has been able to alter its contents by way of deletions, insertions, inversions, and so on. Therefore scientists and researchers are eager to study this bacterium in diverse and unusual niches. Written by experts from around the world, this book describes and discusses the various mechanisms of adaptation and evolution displayed by P. aeruginosa.